Analysis of Needs Response to the Development of Digital Comic on Straight Motion Kinematics Materials - Aulia Nurmalinda Hapsari; Eko Risdianto; Rosane Medriati (IJOEM: Indonesian Journal of E-learning and Multimedia, 2022)
The purpose of this research is to analyze the result of the response to the needs of development digital comics for students. This research is a descriptive research part of R&D research using the ADDIE model. The instruments used are observation sheets, interview sheets, and questionnaire sheets. The subjects consisted of physics teachers and class X students with 147 students and 4 teachers. The instruments used in this study are valid and reliable, students and teachers in 3 high schools in Bengkulu City strongly agree and need digital comic-based learning media with a result obtained being 83,45%.